2018
DOI: 10.4103/aian.aian_17_18
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cluster headache

Abstract: Cluster headache (CH) is a debilitating primary headache disorder. Although uncommon, affecting only 0.1% of population, it is one of the most painful conditions known to humankind. Three strategies are employed for effective treatment of CH, namely, abortive therapy, transitional therapy, and preventive therapy. Being an uncommon condition, there is a paucity of large-scale controlled trials and evidence of various therapies are based on smaller studies. This review primarily focuses on therapies with highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Noninvasive vagal nerve stimulation is well tolerated and has minimal adverse effects, such as short-term discomfort at the site of device application. They stimulate their bodies to treat themselves, and don" t need pharmacologic intervention [26].…”
Section: Non-invasive Vagal Nerve Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive vagal nerve stimulation is well tolerated and has minimal adverse effects, such as short-term discomfort at the site of device application. They stimulate their bodies to treat themselves, and don" t need pharmacologic intervention [26].…”
Section: Non-invasive Vagal Nerve Stimulationmentioning
confidence: 99%
“…SPG stimulation's most common side effects were sensory disturbances and pain due to surgical implantation. This treatment is still under investigation and has not yet been approved by the FDA [26,27].…”
Section: Non-invasive Vagal Nerve Stimulationmentioning
confidence: 99%
“…2 Pharmacological treatments of CH include symptomatic drugs for pain relief, such as triptans and/or high-flow oxygen, and preventive drugs such as verapamil, topiramate, and lithium, which are effective in reducing CH attack frequency. 3 The factors underlying why up to 20%-30% of patients with CH do not benefit from symptomatic and/or preventive drugs remain largely unknown, [4][5][6] but it is widely accepted that interindividual variability of drug responses is explained, at least in part, by genetic factors. 7 Nonetheless, CH has a clear genetic basis as confirmed by family studies, which showed that first-and second-degree relatives of patients with CH have a significantly higher risk of CH compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by strictly unilateral orbital, supraorbital or temporal headaches that severely compromise the quality of life of those who suffer from it. While there are a number of treatments available to alleviate CH symptoms, at least partially [ 1 ], further development is still needed to achieve complete suppression of headache attacks and effective management of commonly associated psychological symptoms (e.g. anxiety, depression).…”
Section: Introductionmentioning
confidence: 99%